h AL-'AULAMAH WA ATSARUHA 'ALA AL-LUGHAH AL-'ARABIYAH - Yeaqub, Md (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This study aimed to investigatet the meaning, concept and development of globalization in term of the cultural aspect, relevant to Arabic Language. It also examined how globalization, as a western product, affected in spreading of Arabic Language in the world. Moreover, it explored that by it, nowadays, how many users are benefited as well as other language throughout the world. It also investigated the nature and the cultural, political and economical senses of the concept. It, furthermore, addressed the positive and negative effects of globalization on the spread of Arabic Language as compared with other international language. In conclusion, the negative effects are apparently more dominant than the positive ones.